Hepatic Steatosis After Neoadjuvant Chemotherapy for Pancreatic Cancer: Incidence and Implications for Outcomes After Pancreatoduodenectomy - Flick, K. F. (J Gastrointest Surg, 2020)
BACKGROUND: This study aimed to determine the incidence of new onset hepatic steatosis after neoadjuvant chemotherapy for pancreatic cancer and its impact on outcomes after pancreatoduodenectomy. METHODS: Retrospective review identified patients who received neoadjuvant chemotherapy for pancreatic adenocarcinoma and underwent pancreatoduodenectomy from 2013 to 2018. Preoperative computed tomography scans were evaluated for the development of hepatic steatosis after neoadjuvant chemotherapy. Hypoattenuation included liver attenuation greater than or equal to 10 Hounsfield units less than tissue density of spleen on noncontrast computed tomography and greater than or equal to 20 Hounsfield units less on contrast-enhanced computed tomography. RESULTS: One hundred forty-nine patients received neoadjuvant chemotherapy for a median of 5 cycles (interquartile range (IQR), 4–6). FOLFIRINOX was the regimen in 78% of patients. Hepatic steatosis developed in 36 (24%) patients. The median time from neoadjuvant chemotherapy completion to pancreatoduodenectomy was 40 days (IQR, 29–51). Preoperative biliary stenting was performed in 126 (86%) patients. Neoadjuvant radiotherapy was delivered to 23 (15%) patients. Female gender, obesity, and prolonged exposure to chemotherapy were identified as risk factors for chemotherapy-associated hepatic steatosis. Compared with control patients without neoadjuvant chemotherapy-associated hepatic steatosis, patients developing steatosis had similar rates of postoperative pancreatic fistula (8% (control) vs. 4%, p = 0.3), delayed gastric emptying (8% vs. 14%, p = 0.4), and major morbidity (11% vs. 15%, p = 0.6). Ninety-day mortality was similar between groups (8% vs. 2%, p = 0.08). CONCLUSION: Hepatic steatosis developed in 24% of patients who received neoadjuvant chemotherapy but was not associated with increased morbidity or mortality after pancreatoduodenectomy.